edits
[lambda.git] / zipper-lists-continuations.mdwn
index 581cdf4..08170a3 100644 (file)
@@ -1,17 +1,20 @@
+
+[[!toc]]
+
 Today we're going to encounter continuations.  We're going to come at
 them from three different directions, and each time we're going to end
 up at the same place: a particular monad, which we'll call the
 continuation monad.
 
 Today we're going to encounter continuations.  We're going to come at
 them from three different directions, and each time we're going to end
 up at the same place: a particular monad, which we'll call the
 continuation monad.
 
-The three approches are:
+Much of this discussion benefited from detailed comments and
+suggestions from Ken Shan.
 
 
-[[!toc]]
 
 Rethinking the list monad
 -------------------------
 
 To construct a monad, the key element is to settle on a type
 
 Rethinking the list monad
 -------------------------
 
 To construct a monad, the key element is to settle on a type
-constructor, and the monad naturally follows from that.  I'll remind
+constructor, and the monad naturally follows from that.  We'll remind
 you of some examples of how monads follow from the type constructor in
 a moment.  This will involve some review of familair material, but
 it's worth doing for two reasons: it will set up a pattern for the new
 you of some examples of how monads follow from the type constructor in
 a moment.  This will involve some review of familair material, but
 it's worth doing for two reasons: it will set up a pattern for the new
@@ -22,73 +25,77 @@ and monads).
 For instance, take the **Reader Monad**.  Once we decide that the type
 constructor is
 
 For instance, take the **Reader Monad**.  Once we decide that the type
 constructor is
 
-    type 'a reader = fun e:env -> 'a
+    type 'a reader = env -> 'a
 
 
-then we can deduce the unit and the bind:
+then the choice of unit and bind is natural:
 
 
-    r_unit x:'a -> 'a reader = fun (e:env) -> x
+    let r_unit (a : 'a) : 'a reader = fun (e : env) -> a
 
 
-Since the type of an `'a reader` is `fun e:env -> 'a` (by definition),
-the type of the `r_unit` function is `'a -> e:env -> 'a`, which is a
-specific case of the type of the *K* combinator.  So it makes sense
+Since the type of an `'a reader` is `env -> 'a` (by definition),
+the type of the `r_unit` function is `'a -> env -> 'a`, which is a
+specific case of the type of the *K* combinator.  It makes sense
 that *K* is the unit for the reader monad.
 
 Since the type of the `bind` operator is required to be
 
 that *K* is the unit for the reader monad.
 
 Since the type of the `bind` operator is required to be
 
-    r_bind:('a reader) -> ('a -> 'b reader) -> ('b reader)
+    r_bind : ('a reader) -> ('a -> 'b reader) -> ('b reader)
 
 
-We can deduce the correct `bind` function as follows:
+We can reason our way to the correct `bind` function as follows. We start by declaring the type:
 
 
-    r_bind (u:'a reader) (f:'a -> 'b reader):('b reader) =
+    let r_bind (u : 'a reader) (f : 'a -> 'b reader) : ('b reader) =
 
 
-We have to open up the `u` box and get out the `'a` object in order to
+Now we have to open up the `u` box and get out the `'a` object in order to
 feed it to `f`.  Since `u` is a function from environments to
 objects of type `'a`, the way we open a box in this monad is
 by applying it to an environment:
 
 feed it to `f`.  Since `u` is a function from environments to
 objects of type `'a`, the way we open a box in this monad is
 by applying it to an environment:
 
-         .... f (u e) ...
+       ... f (u e) ...
 
 This subexpression types to `'b reader`, which is good.  The only
 problem is that we invented an environment `e` that we didn't already have ,
 so we have to abstract over that variable to balance the books:
 
 
 This subexpression types to `'b reader`, which is good.  The only
 problem is that we invented an environment `e` that we didn't already have ,
 so we have to abstract over that variable to balance the books:
 
-         fun e -> f (u e) ...
+       fun e -> f (u e) ...
 
 This types to `env -> 'b reader`, but we want to end up with `env ->
 
 This types to `env -> 'b reader`, but we want to end up with `env ->
-'b`.  Once again, the easiest way to turn a `'b reader` into a `'b` is to apply it to
-an environment.  So we end up as follows:
+'b`.  Once again, the easiest way to turn a `'b reader` into a `'b` is to apply it to an environment.  So we end up as follows:
+
+    r_bind (u : 'a reader) (f : 'a -> 'b reader) : ('b reader) =
+               f (u e) e         
 
 
-    r_bind (u:'a reader) (f:'a -> 'b reader):('b reader) = f (u e) e         
+And we're done. This gives us a bind function of the right type. We can then check whether, in combination with the unit function we chose, it satisfies the monad laws, and behaves in the way we intend. And it does.
 
 
-And we're done.
+[The bind we cite here is a condensed version of the careful `let a = u e in ...`
+constructions we provided in earlier lectures.  We use the condensed
+version here in order to emphasize similarities of structure across
+monads.]
 
 
-The **State Monad** is similar.  We somehow intuit that we want to use
-the following type constructor:
+The **State Monad** is similar.  Once we've decided to use the following type constructor:
 
 
-    type 'a state = 'store -> ('a, 'store)
+    type 'a state = store -> ('a, store)
 
 
-So our unit is naturally
+Then our unit is naturally:
 
 
-    let s_unit (x:'a):('a state) = fun (s:'store) -> (x, s)
+    let s_unit (a : 'a) : ('a state) = fun (s : store) -> (a, s)
 
 
-And we deduce the bind in a way similar to the reasoning given above.
-First, we need to apply `f` to the contents of the `u` box:
+And we can reason our way to the bind function in a way similar to the reasoning given above. First, we need to apply `f` to the contents of the `u` box:
 
 
-    let s_bind (u:'a state) (f:'a -> ('b state)):('b state) = 
+    let s_bind (u : 'a state) (f : 'a -> 'b state) : 'b state = 
+               ... f (...) ...
 
 But unlocking the `u` box is a little more complicated.  As before, we
 need to posit a state `s` that we can apply `u` to.  Once we do so,
 however, we won't have an `'a`, we'll have a pair whose first element
 is an `'a`.  So we have to unpack the pair:
 
 
 But unlocking the `u` box is a little more complicated.  As before, we
 need to posit a state `s` that we can apply `u` to.  Once we do so,
 however, we won't have an `'a`, we'll have a pair whose first element
 is an `'a`.  So we have to unpack the pair:
 
-        ... let (a, s') = u s in ... (f a) ...
+       ... let (a, s') = u s in ... (f a) ...
 
 Abstracting over the `s` and adjusting the types gives the result:
 
 
 Abstracting over the `s` and adjusting the types gives the result:
 
-    let s_bind (u:'a state) (f:'a -> ('b state)):('b state) = 
-      fun (s:state) -> let (a, s') = u s in f a s'
+       let s_bind (u : 'a state) (f : 'a -> 'b state) : 'b state = 
+               fun (s : store) -> let (a, s') = u s in f a s'
 
 
-The **Option Monad** doesn't follow the same pattern so closely, so we
+The **Option/Maybe Monad** doesn't follow the same pattern so closely, so we
 won't pause to explore it here, though conceptually its unit and bind
 follow just as naturally from its type constructor.
 
 won't pause to explore it here, though conceptually its unit and bind
 follow just as naturally from its type constructor.
 
@@ -96,10 +103,13 @@ Our other familiar monad is the **List Monad**, which we were told
 looks like this:
 
     type 'a list = ['a];;
 looks like this:
 
     type 'a list = ['a];;
-    l_unit (x:'a) = [x];;
+    l_unit (a : 'a) = [a];;
     l_bind u f = List.concat (List.map f u);;
 
     l_bind u f = List.concat (List.map f u);;
 
-Recall that `List.map` take a function and a list and returns the
+Thinking through the list monad will take a little time, but doing so
+will provide a connection with continuations.
+
+Recall that `List.map` takes a function and a list and returns the
 result to applying the function to the elements of the list:
 
     List.map (fun i -> [i;i+1]) [1;2] ~~> [[1; 2]; [2; 3]]
 result to applying the function to the elements of the list:
 
     List.map (fun i -> [i;i+1]) [1;2] ~~> [[1; 2]; [2; 3]]
@@ -113,46 +123,60 @@ And sure enough,
 
     l_bind [1;2] (fun i -> [i, i+1]) ~~> [1; 2; 2; 3]
 
 
     l_bind [1;2] (fun i -> [i, i+1]) ~~> [1; 2; 2; 3]
 
-But where is the reasoning that led us to this unit and bind?
-And what is the type `['a]`?  Magic.
-
-So let's take a *completely useless digressing* and see if we can
-gain some insight into the details of the List monad.  Let's choose
-type constructor that we can peer into, using some of the technology
-we built up so laboriously during the first half of the course.  I'm
-going to use type 3 lists, partly because I know they'll give the
-result I want, but also because they're my favorite.  These were the
-lists that made lists look like Church numerals with extra bits
-embdded in them:
+Now, why this unit, and why this bind?  Well, ideally a unit should
+not throw away information, so we can rule out `fun x -> []` as an
+ideal unit.  And units should not add more information than required,
+so there's no obvious reason to prefer `fun x -> [x,x]`.  In other
+words, `fun x -> [x]` is a reasonable guess for a unit.
+
+As for bind, an `'a list` monadic object contains a lot of objects of
+type `'a`, and we want to make some use of each of them.  The only
+thing we know for sure we can do with an object of type `'a` is apply
+the function of type `'a -> 'a list` to them.  Once we've done so, we
+have a collection of lists, one for each of the `'a`'s.  One
+possibility is that we could gather them all up in a list, so that
+`bind' [1;2] (fun i -> [i;i]) ~~> [[1;1];[2;2]]`.  But that restricts
+the object returned by the second argument of `bind` to always be of
+type `'b list list`.  We can elimiate that restriction by flattening
+the list of lists into a single list.  So there is some logic to the
+choice of unit and bind for the list monad.  
+
+Yet we can still desire to go deeper, and see if the appropriate bind
+behavior emerges from the types, as it did for the previously
+considered monads.  But we can't do that if we leave the list type is
+a primitive Ocaml type.  However, we know several ways of implementing
+lists using just functions.  In what follows, we're going to use type
+3 lists (the right fold implementation), though it's important to
+wonder how things would change if we used some other strategy for
+implementating lists.  These were the lists that made lists look like
+Church numerals with extra bits embdded in them:
 
     empty list:                fun f z -> z
     list with one element:     fun f z -> f 1 z
     list with two elements:    fun f z -> f 2 (f 1 z)
     list with three elements:  fun f z -> f 3 (f 2 (f 1 z))
 
 
     empty list:                fun f z -> z
     list with one element:     fun f z -> f 1 z
     list with two elements:    fun f z -> f 2 (f 1 z)
     list with three elements:  fun f z -> f 3 (f 2 (f 1 z))
 
-and so on.  To save time, we'll let the Ocaml interpreter infer the
+and so on.  To save time, we'll let the OCaml interpreter infer the
 principle types of these functions (rather than deducing what the
 types should be):
 
 principle types of these functions (rather than deducing what the
 types should be):
 
-<pre>
-# fun f z -> z;;
-- : 'a -> 'b -> 'b = <fun>
-# fun f z -> f 1 z;;
-- : (int -> 'a -> 'b) -> 'a -> 'b = <fun>
-# fun f z -> f 2 (f 1 z);;
-- : (int -> 'a -> 'a) -> 'a -> 'a = <fun>
-# fun f z -> f 3 (f 2 (f 1 z))
-- : (int -> 'a -> 'a) -> 'a -> 'a = <fun>
-</pre>
+       # fun f z -> z;;
+       - : 'a -> 'b -> 'b = <fun>
+       # fun f z -> f 1 z;;
+       - : (int -> 'a -> 'b) -> 'a -> 'b = <fun>
+       # fun f z -> f 2 (f 1 z);;
+       - : (int -> 'a -> 'a) -> 'a -> 'a = <fun>
+       # fun f z -> f 3 (f 2 (f 1 z))
+       - : (int -> 'a -> 'a) -> 'a -> 'a = <fun>
 
 
-Finally, we're getting consistent principle types, so we can stop.
-These types should remind you of the simply-typed lambda calculus
-types for Church numerals (`(o -> o) -> o -> o`) with one extra bit
-thrown in (in this case, and int).
+We can see what the consistent, general principle types are at the end, so we
+can stop. These types should remind you of the simply-typed lambda calculus
+types for Church numerals (`(o -> o) -> o -> o`) with one extra bit thrown in
+(in this case, an int).
 
 So here's our type constructor for our hand-rolled lists:
 
 
 So here's our type constructor for our hand-rolled lists:
 
-    type 'a list' = (int -> 'a -> 'a) -> 'a -> 'a
+    type 'b list' = (int -> 'b -> 'b) -> 'b -> 'b
 
 Generalizing to lists that contain any kind of element (not just
 ints), we have
 
 Generalizing to lists that contain any kind of element (not just
 ints), we have
@@ -161,63 +185,104 @@ ints), we have
 
 So an `('a, 'b) list'` is a list containing elements of type `'a`,
 where `'b` is the type of some part of the plumbing.  This is more
 
 So an `('a, 'b) list'` is a list containing elements of type `'a`,
 where `'b` is the type of some part of the plumbing.  This is more
-general than an ordinary Ocaml list, but we'll see how to map them
-into Ocaml lists soon.  We don't need to grasp the role of the `'b`'s
+general than an ordinary OCaml list, but we'll see how to map them
+into OCaml lists soon.  We don't need to fully grasp the role of the `'b`'s
 in order to proceed to build a monad:
 
 in order to proceed to build a monad:
 
-    l'_unit (x:'a):(('a, 'b) list) = fun x -> fun f z -> f x z
+    l'_unit (a : 'a) : ('a, 'b) list = fun a -> fun f z -> f a z
 
 No problem.  Arriving at bind is a little more complicated, but
 exactly the same principles apply, you just have to be careful and
 systematic about it.
 
 
 No problem.  Arriving at bind is a little more complicated, but
 exactly the same principles apply, you just have to be careful and
 systematic about it.
 
-    l'_bind (u:('a,'b) list') (f:'a -> ('c, 'd) list'): ('c, 'd) list'  = ...
+    l'_bind (u : ('a,'b) list') (f : 'a -> ('c, 'd) list') : ('c, 'd) list'  = ...
 
 
-Unfortunately, we'll need to spell out the types:
+Unpacking the types gives:
 
 
-    l'_bind (u: ('a -> 'b -> 'b) -> 'b -> 'b)
-            (f: 'a -> ('c -> 'd -> 'd) -> 'd -> 'd)
+    l'_bind (u : ('a -> 'b -> 'b) -> 'b -> 'b)
+            (f : 'a -> ('c -> 'd -> 'd) -> 'd -> 'd)
             : ('c -> 'd -> 'd) -> 'd -> 'd = ...
 
             : ('c -> 'd -> 'd) -> 'd -> 'd = ...
 
-It's a rookie mistake to quail before complicated types.  You should
+But it's a rookie mistake to quail before complicated types. You should
 be no more intimiated by complex types than by a linguistic tree with
 deeply embedded branches: complex structure created by repeated
 application of simple rules.
 
 As usual, we need to unpack the `u` box.  Examine the type of `u`.
 This time, `u` will only deliver up its contents if we give `u` as an
 be no more intimiated by complex types than by a linguistic tree with
 deeply embedded branches: complex structure created by repeated
 application of simple rules.
 
 As usual, we need to unpack the `u` box.  Examine the type of `u`.
 This time, `u` will only deliver up its contents if we give `u` as an
-argument a function expecting an `'a`.  Once that argument is applied
-to an object of type `'a`, we'll have what we need.  Thus:
+argument a function expecting an `'a` and a `'b`. `u` will fold that function over its type `'a` members, and that's how we'll get the `'a`s we need. Thus:
 
 
-      .... u (fun (x:'a) -> ... (f a) ... ) ...
+       ... u (fun (a : 'a) (b : 'b) -> ... f a ... ) ...
 
 
-In order for `u` to have the kind of argument it needs, we have to
-adjust `(f a)` (which has type `('c -> 'd -> 'd) -> 'd -> 'd`) in
-order to deliver something of type `'b -> 'b`.  The easiest way is to
-alias `'d` to `'b`, and provide `(f a)` with an argument of type `'c
--> 'b -> 'b`.  Thus:
+In order for `u` to have the kind of argument it needs, the `... (f a) ...` has to evaluate to a result of type `'b`. The easiest way to do this is to collapse (or "unify") the types `'b` and `'d`, with the result that `f a` will have type `('c -> 'b -> 'b) -> 'b -> 'b`. Let's postulate an argument `k` of type `('c -> 'b -> 'b)` and supply it to `(f a)`:
 
 
-    l'_bind (u: ('a -> 'b -> 'b) -> 'b -> 'b)
-            (f: 'a -> ('c -> 'b -> 'b) -> 'b -> 'b)
-            : ('c -> 'b -> 'b) -> 'b -> 'b = 
-      .... u (fun (x:'a) -> f a k) ...
+       ... u (fun (a : 'a) (b : 'b) -> ... f a k ... ) ...
 
 
-[Excercise: can you arrive at a fully general bind for this type
-constructor, one that does not collapse `'d`'s with `'b`'s?]
+Now we have an argument `b` of type `'b`, so we can supply that to `(f a) k`, getting a result of type `'b`, as we need:
 
 
-As usual, we have to abstract over `k`, but this time, no further
-adjustments are needed:
+       ... u (fun (a : 'a) (b : 'b) -> f a k b) ...
 
 
-    l'_bind (u: ('a -> 'b -> 'b) -> 'b -> 'b)
-            (f: 'a -> ('c -> 'b -> 'b) -> 'b -> 'b)
+Now, we've used a `k` that we pulled out of nowhere, so we need to abstract over it:
+
+       fun (k : 'c -> 'b -> 'b) -> u (fun (a : 'a) (b : 'b) -> f a k b)
+
+This whole expression has type `('c -> 'b -> 'b) -> 'b -> 'b`, which is exactly the type of a `('c, 'b) list'`. So we can hypothesize that we our bind is:
+
+    l'_bind (u : ('a -> 'b -> 'b) -> 'b -> 'b)
+            (f : 'a -> ('c -> 'b -> 'b) -> 'b -> 'b)
             : ('c -> 'b -> 'b) -> 'b -> 'b = 
             : ('c -> 'b -> 'b) -> 'b -> 'b = 
-      fun (k:'c -> 'b -> 'b) -> u (fun (x:'a) -> f a k)
+      fun k -> u (fun a b -> f a k b)
+
+That is a function of the right type for our bind, but to check whether it works, we have to verify it (with the unit we chose) against the monad laws, and reason whether it will have the right behavior.
+
+Here's a way to persuade yourself that it will have the right behavior. First, it will be handy to eta-expand our `fun k -> u (fun a b -> f a k b)` to:
+
+      fun k z -> u (fun a b -> f a k b) z
+
+Now let's think about what this does. It's a wrapper around `u`. In order to behave as the list which is the result of mapping `f` over each element of `u`, and then joining (`concat`ing) the results, this wrapper would have to accept arguments `k` and `z` and fold them in just the same way that the list which is the result of mapping `f` and then joining the results would fold them. Will it?
+
+Suppose we have a list' whose contents are `[1; 2; 4; 8]`---that is, our list' will be `fun f z -> f 1 (f 2 (f 4 (f 8 z)))`. We call that list' `u`. Suppose we also have a function `f` that for each `int` we give it, gives back a list of the divisors of that `int` that are greater than 1. Intuitively, then, binding `u` to `f` should give us:
+
+       concat (map f u) =
+       concat [[]; [2]; [2; 4]; [2; 4; 8]] =
+       [2; 2; 4; 2; 4; 8]
 
 
-You should carefully check to make sure that this term is consistent
-with the typing.
+Or rather, it should give us a list' version of that, which takes a function `k` and value `z` as arguments, and returns the right fold of `k` and `z` over those elements. What does our formula
 
 
-Our theory is that this monad should be capable of exactly
-replicating the behavior of the standard List monad.  Let's test:
+      fun k z -> u (fun a b -> f a k b) z
+       
+do? Well, for each element `a` in `u`, it applies `f` to that `a`, getting one of the lists:
+
+       []
+       [2]
+       [2; 4]
+       [2; 4; 8]
+
+(or rather, their list' versions). Then it takes the accumulated result `b` of previous steps in the fold, and it folds `k` and `b` over the list generated by `f a`. The result of doing so is passed on to the next step as the accumulated result so far.
+
+So if, for example, we let `k` be `+` and `z` be `0`, then the computation would proceed:
+
+       0 ==>
+       right-fold + and 0 over [2; 4; 8] = 2+4+8+0 ==>
+       right-fold + and 2+4+8+0 over [2; 4] = 2+4+2+4+8+0 ==>
+       right-fold + and 2+4+2+4+8+0 over [2] = 2+2+4+2+4+8+0 ==>
+       right-fold + and 2+2+4+2+4+8+0 over [] = 2+2+4+2+4+8+0
+
+which indeed is the result of right-folding + and 0 over `[2; 2; 4; 2; 4; 8]`. If you trace through how this works, you should be able to persuade yourself that our formula:
+
+      fun k z -> u (fun a b -> f a k b) z
+
+will deliver just the same folds, for arbitrary choices of `k` and `z` (with the right types), and arbitrary list's `u` and appropriately-typed `f`s, as
+
+       fun k z -> List.fold_right k (concat (map f u)) z
+
+would.
+
+For future reference, we might make two eta-reductions to our formula, so that we have instead:
+
+      let l'_bind = fun k -> u (fun a -> f a k);;
+
+Let's make some more tests:
 
 
     l_bind [1;2] (fun i -> [i, i+1]) ~~> [1; 2; 2; 3]
 
 
     l_bind [1;2] (fun i -> [i, i+1]) ~~> [1; 2; 2; 3]
@@ -225,29 +290,17 @@ replicating the behavior of the standard List monad.  Let's test:
     l'_bind (fun f z -> f 1 (f 2 z)) 
             (fun i -> fun f z -> f i (f (i+1) z)) ~~> <fun>
 
     l'_bind (fun f z -> f 1 (f 2 z)) 
             (fun i -> fun f z -> f i (f (i+1) z)) ~~> <fun>
 
-Sigh.  Ocaml won't show us our own list.  So we have to choose an `f`
-and a `z` that will turn our hand-crafted lists into standard Ocaml
+Sigh.  OCaml won't show us our own list.  So we have to choose an `f`
+and a `z` that will turn our hand-crafted lists into standard OCaml
 lists, so that they will print out.
 
 lists, so that they will print out.
 
-<pre>
-# let cons h t = h :: t;;  (* Ocaml is stupid about :: *)
-# l'_bind (fun f z -> f 1 (f 2 z)) 
-          (fun i -> fun f z -> f i (f (i+1) z)) cons [];;
-- : int list = [1; 2; 2; 3]
-</pre>
+       # let cons h t = h :: t;;  (* OCaml is stupid about :: *)
+       # l'_bind (fun f z -> f 1 (f 2 z)) 
+                         (fun i -> fun f z -> f i (f (i+1) z)) cons [];;
+       - : int list = [1; 2; 2; 3]
 
 Ta da!
 
 
 Ta da!
 
-Just for mnemonic purposes (sneaking in an instance of eta reduction
-to the definition of unit), we can summarize the result as follows:
-
-    type ('a, 'b) list' = ('a -> 'b -> 'b) -> 'b -> 'b
-    l'_unit x = fun f -> f x
-    l'_bind u f = fun k -> u (fun x -> f x k)
-
-To bad this digression, though it ties together various
-elements of the course, has *no relevance whatsoever* to the topic of
-continuations.
 
 Montague's PTQ treatment of DPs as generalized quantifiers
 ----------------------------------------------------------
 
 Montague's PTQ treatment of DPs as generalized quantifiers
 ----------------------------------------------------------
@@ -265,46 +318,434 @@ generalized quantifier `fun pred -> pred j` of type `(e -> t) -> t`.
 Let's write a general function that will map individuals into their
 corresponding generalized quantifier:
 
 Let's write a general function that will map individuals into their
 corresponding generalized quantifier:
 
-   gqize (x:e) = fun (p:e->t) -> p x
+   gqize (a : e) = fun (p : e -> t) -> p a
 
 This function wraps up an individual in a fancy box.  That is to say,
 we are in the presence of a monad.  The type constructor, the unit and
 
 This function wraps up an individual in a fancy box.  That is to say,
 we are in the presence of a monad.  The type constructor, the unit and
-the bind follow naturally.  We've done this enough times that I won't
+the bind follow naturally.  We've done this enough times that we won't
 belabor the construction of the bind function, the derivation is
 similar to the List monad just given:
 
 belabor the construction of the bind function, the derivation is
 similar to the List monad just given:
 
-   type 'a continuation = ('a -> 'b) -> 'b
-   c_unit (x:'a) = fun (p:'a -> 'b) -> p x
-   c_bind (u:('a -> 'b) -> 'b) (f: 'a -> ('c -> 'd) -> 'd): ('c -> 'd) -> 'd =
-     fun (k:'a -> 'b) -> u (fun (x:'a) -> f x k)
+       type 'a continuation = ('a -> 'b) -> 'b
+       c_unit (a : 'a) = fun (p : 'a -> 'b) -> p a
+       c_bind (u : ('a -> 'b) -> 'b) (f : 'a -> ('c -> 'd) -> 'd) : ('c -> 'd) -> 'd =
+         fun (k : 'a -> 'b) -> u (fun (a : 'a) -> f a k)
 
 How similar is it to the List monad?  Let's examine the type
 constructor and the terms from the list monad derived above:
 
     type ('a, 'b) list' = ('a -> 'b -> 'b) -> 'b -> 'b
 
 How similar is it to the List monad?  Let's examine the type
 constructor and the terms from the list monad derived above:
 
     type ('a, 'b) list' = ('a -> 'b -> 'b) -> 'b -> 'b
-    l'_unit x = fun f -> f x                 
-    l'_bind u f = fun k -> u (fun x -> f x k)
+    l'_unit a = fun f -> f a                 
+    l'_bind u f = fun k -> u (fun a -> f a k)
 
 
-(I performed a sneaky but valid eta reduction in the unit term.)
+(We performed a sneaky but valid eta reduction in the unit term.)
 
 The unit and the bind for the Montague continuation monad and the
 homemade List monad are the same terms!  In other words, the behavior
 of the List monad and the behavior of the continuations monad are
 
 The unit and the bind for the Montague continuation monad and the
 homemade List monad are the same terms!  In other words, the behavior
 of the List monad and the behavior of the continuations monad are
-parallel in a deep sense.  To emphasize the parallel, we can
-instantiate the type of the list' monad using the Ocaml list type:
-
-    type 'a c_list = ('a -> 'a list) -> 'a list
-    let c_list_unit x = fun f -> f x;;
-    let c_list_bind u f = fun k -> u (fun x -> f x k);;
+parallel in a deep sense.
 
 
-Have we really discovered that lists are secretly continuations?
-Or have we merely found a way of simulating lists using list
-continuations?  Both perspectives are valid, and we can use our
-intuitions about the list monad to understand continuations, and vice
-versa.  The connections will be expecially relevant when we consider 
-indefinites and Hamblin semantics on the linguistic side, and
-non-determinism on the list monad side.
+Have we really discovered that lists are secretly continuations?  Or
+have we merely found a way of simulating lists using list
+continuations?  Well, strictly speaking, what we have done is shown
+that one particular implementation of lists---the left fold
+implementation---gives rise to a continuation monad fairly naturally,
+and that this monad can reproduce the behavior of the standard list
+monad.  But what about other list implementations?  Do they give rise
+to monads that can be understood in terms of continuations?
 
 Refunctionalizing zippers
 -------------------------
 
 
 Refunctionalizing zippers
 -------------------------
 
+Manipulating trees with monads
+------------------------------
+
+This thread develops an idea based on a detailed suggestion of Ken
+Shan's.  We'll build a series of functions that operate on trees,
+doing various things, including replacing leaves, counting nodes, and
+converting a tree to a list of leaves.  The end result will be an
+application for continuations.
+
+From an engineering standpoint, we'll build a tree transformer that
+deals in monads.  We can modify the behavior of the system by swapping
+one monad for another.  (We've already seen how adding a monad can add
+a layer of funtionality without disturbing the underlying system, for
+instance, in the way that the reader monad allowed us to add a layer
+of intensionality to an extensional grammar, but we have not yet seen
+the utility of replacing one monad with other.)
+
+First, we'll be needing a lot of trees during the remainder of the
+course.  Here's a type constructor for binary trees:
+
+    type 'a tree = Leaf of 'a | Node of ('a tree * 'a tree)
+
+These are trees in which the internal nodes do not have labels.  [How
+would you adjust the type constructor to allow for labels on the
+internal nodes?]
+
+We'll be using trees where the nodes are integers, e.g.,
+
+
+<pre>
+let t1 = Node ((Node ((Leaf 2), (Leaf 3))),
+               (Node ((Leaf 5),(Node ((Leaf 7),
+                                      (Leaf 11))))))
+
+    .
+ ___|___
+ |     |
+ .     .
+_|__  _|__
+|  |  |  |
+2  3  5  .
+        _|__
+        |  |
+        7  11
+</pre>
+
+Our first task will be to replace each leaf with its double:
+
+<pre>
+let rec treemap (newleaf:'a -> 'b) (t:'a tree):('b tree) =
+  match t with Leaf x -> Leaf (newleaf x)
+             | Node (l, r) -> Node ((treemap newleaf l),
+                                    (treemap newleaf r));;
+</pre>
+`treemap` takes a function that transforms old leaves into new leaves, 
+and maps that function over all the leaves in the tree, leaving the
+structure of the tree unchanged.  For instance:
+
+<pre>
+let double i = i + i;;
+treemap double t1;;
+- : int tree =
+Node (Node (Leaf 4, Leaf 6), Node (Leaf 10, Node (Leaf 14, Leaf 22)))
+
+    .
+ ___|____
+ |      |
+ .      .
+_|__  __|__
+|  |  |   |
+4  6  10  .
+        __|___
+        |    |
+        14   22
+</pre>
+
+We could have built the doubling operation right into the `treemap`
+code.  However, because what to do to each leaf is a parameter, we can
+decide to do something else to the leaves without needing to rewrite
+`treemap`.  For instance, we can easily square each leaf instead by
+supplying the appropriate `int -> int` operation in place of `double`:
+
+<pre>
+let square x = x * x;;
+treemap square t1;;
+- : int tree =ppp
+Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
+</pre>
+
+Note that what `treemap` does is take some global, contextual
+information---what to do to each leaf---and supplies that information
+to each subpart of the computation.  In other words, `treemap` has the
+behavior of a reader monad.  Let's make that explicit.  
+
+In general, we're on a journey of making our treemap function more and
+more flexible.  So the next step---combining the tree transducer with
+a reader monad---is to have the treemap function return a (monadized)
+tree that is ready to accept any `int->int` function and produce the
+updated tree.
+
+\tree (. (. (f2) (f3))(. (f5) (.(f7)(f11))))
+<pre>
+\f    .
+  ____|____
+  |       |
+  .       .
+__|__   __|__
+|   |   |   |
+f2  f3  f5  .
+          __|___
+          |    |
+          f7  f11
+</pre>
+
+That is, we want to transform the ordinary tree `t1` (of type `int
+tree`) into a reader object of type `(int->int)-> int tree`: something 
+that, when you apply it to an `int->int` function returns an `int
+tree` in which each leaf `x` has been replaced with `(f x)`.
+
+With previous readers, we always knew which kind of environment to
+expect: either an assignment function (the original calculator
+simulation), a world (the intensionality monad), an integer (the
+Jacobson-inspired link monad), etc.  In this situation, it will be
+enough for now to expect that our reader will expect a function of
+type `int->int`.
+
+<pre>
+type 'a reader = (int->int) -> 'a;;  (* mnemonic: e for environment *)
+let reader_unit (x:'a): 'a reader = fun _ -> x;;
+let reader_bind (u: 'a reader) (f:'a -> 'c reader):'c reader = fun e -> f (u e) e;;
+</pre>
+
+It's easy to figure out how to turn an `int` into an `int reader`:
+
+<pre>
+let int2int_reader (x:'a): 'b reader = fun (op:'a -> 'b) -> op x;;
+int2int_reader 2 (fun i -> i + i);;
+- : int = 4
+</pre>
+
+But what do we do when the integers are scattered over the leaves of a
+tree?  A binary tree is not the kind of thing that we can apply a
+function of type `int->int` to.
+
+<pre>
+let rec treemonadizer (f:'a -> 'b reader) (t:'a tree):('b tree) reader =
+  match t with Leaf x -> reader_bind (f x) (fun x' -> reader_unit (Leaf x'))
+             | Node (l, r) -> reader_bind (treemonadizer f l) (fun x ->
+                                reader_bind (treemonadizer f r) (fun y ->
+                                  reader_unit (Node (x, y))));;
+</pre>
+
+This function says: give me a function `f` that knows how to turn
+something of type `'a` into an `'b reader`, and I'll show you how to 
+turn an `'a tree` into an `'a tree reader`.  In more fanciful terms, 
+the `treemonadizer` function builds plumbing that connects all of the
+leaves of a tree into one connected monadic network; it threads the
+monad through the leaves.
+
+<pre>
+# treemonadizer int2int_reader t1 (fun i -> i + i);;
+- : int tree =
+Node (Node (Leaf 4, Leaf 6), Node (Leaf 10, Node (Leaf 14, Leaf 22)))
+</pre>
+
+Here, our environment is the doubling function (`fun i -> i + i`).  If
+we apply the very same `int tree reader` (namely, `treemonadizer
+int2int_reader t1`) to a different `int->int` function---say, the
+squaring function, `fun i -> i * i`---we get an entirely different
+result:
+
+<pre>
+# treemonadizer int2int_reader t1 (fun i -> i * i);;
+- : int tree =
+Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
+</pre>
+
+Now that we have a tree transducer that accepts a monad as a
+parameter, we can see what it would take to swap in a different monad.
+For instance, we can use a state monad to count the number of nodes in
+the tree.
+
+<pre>
+type 'a state = int -> 'a * int;;
+let state_unit x i = (x, i+.5);;
+let state_bind u f i = let (a, i') = u i in f a (i'+.5);;
+</pre>
+
+Gratifyingly, we can use the `treemonadizer` function without any
+modification whatsoever, except for replacing the (parametric) type
+`reader` with `state`:
+
+<pre>
+let rec treemonadizer (f:'a -> 'b state) (t:'a tree):('b tree) state =
+  match t with Leaf x -> state_bind (f x) (fun x' -> state_unit (Leaf x'))
+             | Node (l, r) -> state_bind (treemonadizer f l) (fun x ->
+                                state_bind (treemonadizer f r) (fun y ->
+                                  state_unit (Node (x, y))));;
+</pre>
+
+Then we can count the number of nodes in the tree:
+
+<pre>
+# treemonadizer state_unit t1 0;;
+- : int tree * int =
+(Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11))), 13)
+
+    .
+ ___|___
+ |     |
+ .     .
+_|__  _|__
+|  |  |  |
+2  3  5  .
+        _|__
+        |  |
+        7  11
+</pre>
+
+Notice that we've counted each internal node twice---it's a good
+exercise to adjust the code to count each node once.
+
+One more revealing example before getting down to business: replacing
+`state` everywhere in `treemonadizer` with `list` gives us
+
+<pre>
+# treemonadizer (fun x -> [ [x; square x] ]) t1;;
+- : int list tree list =
+[Node
+  (Node (Leaf [2; 4], Leaf [3; 9]),
+   Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))]
+</pre>
+
+Unlike the previous cases, instead of turning a tree into a function
+from some input to a result, this transformer replaces each `int` with
+a list of `int`'s.
+
+Now for the main point.  What if we wanted to convert a tree to a list
+of leaves?  
+
+<pre>
+type ('a, 'r) continuation = ('a -> 'r) -> 'r;;
+let continuation_unit x c = c x;;
+let continuation_bind u f c = u (fun a -> f a c);;
+
+let rec treemonadizer (f:'a -> ('b, 'r) continuation) (t:'a tree):(('b tree), 'r) continuation =
+  match t with Leaf x -> continuation_bind (f x) (fun x' -> continuation_unit (Leaf x'))
+             | Node (l, r) -> continuation_bind (treemonadizer f l) (fun x ->
+                                continuation_bind (treemonadizer f r) (fun y ->
+                                  continuation_unit (Node (x, y))));;
+</pre>
+
+We use the continuation monad described above, and insert the
+`continuation` type in the appropriate place in the `treemonadizer` code.
+We then compute:
+
+<pre>
+# treemonadizer (fun a c -> a :: (c a)) t1 (fun t -> []);;
+- : int list = [2; 3; 5; 7; 11]
+</pre>
+
+We have found a way of collapsing a tree into a list of its leaves.
+
+The continuation monad is amazingly flexible; we can use it to
+simulate some of the computations performed above.  To see how, first
+note that an interestingly uninteresting thing happens if we use the
+continuation unit as our first argument to `treemonadizer`, and then
+apply the result to the identity function:
+
+<pre>
+# treemonadizer continuation_unit t1 (fun x -> x);;
+- : int tree =
+Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11)))
+</pre>
+
+That is, nothing happens.  But we can begin to substitute more
+interesting functions for the first argument of `treemonadizer`:
+
+<pre>
+(* Simulating the tree reader: distributing a operation over the leaves *)
+# treemonadizer (fun a c -> c (square a)) t1 (fun x -> x);;
+- : int tree =
+Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
+
+(* Simulating the int list tree list *)
+# treemonadizer (fun a c -> c [a; square a]) t1 (fun x -> x);;
+- : int list tree =
+Node
+ (Node (Leaf [2; 4], Leaf [3; 9]),
+  Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))
+
+(* Counting leaves *)
+# treemonadizer (fun a c -> 1 + c a) t1 (fun x -> 0);;
+- : int = 5
+</pre>
+
+We could simulate the tree state example too, but it would require
+generalizing the type of the continuation monad to 
+
+    type ('a -> 'b -> 'c) continuation = ('a -> 'b) -> 'c;;
+
+The binary tree monad
+---------------------
+
+Of course, by now you may have realized that we have discovered a new
+monad, the binary tree monad:
+
+<pre>
+type 'a tree = Leaf of 'a | Node of ('a tree) * ('a tree);;
+let tree_unit (x:'a) = Leaf x;;
+let rec tree_bind (u:'a tree) (f:'a -> 'b tree):'b tree = 
+  match u with Leaf x -> f x 
+             | Node (l, r) -> Node ((tree_bind l f), (tree_bind r f));;
+</pre>
+
+For once, let's check the Monad laws.  The left identity law is easy:
+
+    Left identity: bind (unit a) f = bind (Leaf a) f = fa
+
+To check the other two laws, we need to make the following
+observation: it is easy to prove based on `tree_bind` by a simple
+induction on the structure of the first argument that the tree
+resulting from `bind u f` is a tree with the same strucure as `u`,
+except that each leaf `a` has been replaced with `fa`:
+
+\tree (. (fa1) (. (. (. (fa2)(fa3)) (fa4)) (fa5)))
+<pre>
+                .                         .       
+              __|__                     __|__   
+              |   |                     |   |   
+              a1  .                    fa1  .   
+                 _|__                     __|__ 
+                 |  |                     |   | 
+                 .  a5                    .  fa5
+   bind         _|__       f   =        __|__   
+                |  |                    |   |   
+                .  a4                   .  fa4  
+              __|__                   __|___   
+              |   |                   |    |   
+              a2  a3                 fa2  fa3         
+</pre>   
+
+Given this equivalence, the right identity law
+
+    Right identity: bind u unit = u
+
+falls out once we realize that
+
+    bind (Leaf a) unit = unit a = Leaf a
+
+As for the associative law,
+
+    Associativity: bind (bind u f) g = bind u (\a. bind (fa) g)
+
+we'll give an example that will show how an inductive proof would
+proceed.  Let `f a = Node (Leaf a, Leaf a)`.  Then
+
+\tree (. (. (. (. (a1)(a2)))))
+\tree (. (. (. (. (a1) (a1)) (. (a1) (a1)))  ))
+<pre>
+                                           .
+                                       ____|____
+          .               .            |       |
+bind    __|__   f  =    __|_    =      .       .
+        |   |           |   |        __|__   __|__
+        a1  a2         fa1 fa2       |   |   |   |
+                                     a1  a1  a1  a1  
+</pre>
+
+Now when we bind this tree to `g`, we get
+
+<pre>
+           .
+       ____|____
+       |       |
+       .       .
+     __|__   __|__
+     |   |   |   |
+    ga1 ga1 ga1 ga1  
+</pre>
+
+At this point, it should be easy to convince yourself that
+using the recipe on the right hand side of the associative law will
+built the exact same final tree.
+
+So binary trees are a monad.
+
+Haskell combines this monad with the Option monad to provide a monad
+called a
+[SearchTree](http://hackage.haskell.org/packages/archive/tree-monad/0.2.1/doc/html/src/Control-Monad-SearchTree.html#SearchTree)
+that is intended to 
+represent non-deterministic computations as a tree.